The impact of business measurement system on organizational performance - Ma, Jih Jing (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The general objective of this study was to investigate the impact of business measurement system on organizational performance. Specifically, the purpose of this study was to examine the influence of operational performance measurement (OPM), empowerment measurement (EM), integration measurement (IM) and strategic alignment measurement (SAM) on organizational performance. The study was conducted on the financial institutions based in Malaysia. Four broadly hypothesized relationships were tested and data were collected by means of questionnaires. Data collected through questionnaires in this research were analyzed using Statistical Package for Social Sciences (SPSS) Version 19.0 and SmartPLS 2.0. Test such as confirmatory factor analysis (CFA), convergent validity, discriminant validity, and reliability test were carried out to assess measurement model, whereas t-value test used to assess structural model. The results showed that OPM and SAM were significantly related to organizational performance, whereas EM and 1M were not significantly related to organizational performance. This study have revealed the employees view of business measurement system on organizational performance and provided both theoretical and practical implications that could be very beneficial to scholars and practitioners.